Hollow fiber earthworm ultrafiltration membrane for Qilong capsule and preparation process of hollow fiber earthworm ultrafiltration membrane
The hollow fiber Dilong ultrafiltration membrane prepared by composite polyether sulfone and other materials solves the problems of blockage and insufficient anti-pollution performance of ultrafiltration membranes in the prior art, and achieves the improvement of high hydrophilicity, anti-pollution performance and effective component interception rate.
Patent Information
- Application Number
- CN202411520953.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-04
AI Technical Summary
In the prior art, hollow fiber ultrafiltration membranes are easily blocked during the preparation of Qilong capsules, resulting in a decrease in membrane flux and a decrease in the retention rate of active ingredients. At the same time, microbial adhesion and deposition on the surface of the membrane are prone to occur, affecting the anti-pollution performance.
By combining polyether sulfone, modified polyacrylonitrile, carboxylated polyethyleneimine, polyethylene glycol, functional fillers and glutaraldehyde, a hollow fiber dilong ultrafiltration membrane for Qilong capsules was prepared, which improved the hydrophilicity and anti-pollution performance of the membrane, reduced microbial adhesion and deposition, and ensured the membrane flux and retention rate of active ingredients.
It improves the hydrophilicity and anti-pollution properties of the ultrafiltration membrane, extends the service life of the membrane, ensures the retention rate of active ingredients in the dinosaur extract, and maintains efficient membrane flux.
Smart Images

Figure BDA0005108029450000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of Qilong capsule production, and in particular to a hollow fiber earthworm ultrafiltration membrane for Qilong capsule and a preparation process thereof. Background Art
[0002] Ultrafiltration technology is a membrane separation technology between microfiltration and nanofiltration, with an average pore size of 3 to 100 nm, and has the functions of purifying, separating, and concentrating solutions. Its interception mechanism mainly includes the screening effect and electrostatic effect of the membrane. The filtration medium is an ultrafiltration membrane. Driven by the pressure difference on both sides, only low molecular weight solutes and water can pass through the ultrafiltration membrane, thereby achieving the purpose of purification, separation, and concentration.
[0003] During the preparation of Qilong capsules, the extract of earthworms needs to be subjected to ultrafiltration interception treatment. The earthworm extract contains collagenase, fibrinolytic enzyme, lumbrokinase, nucleic acid, trace elements and other components. During the ultrafiltration process, the hollow fiber membrane is easy to cause blockage after multiple membrane separation processes due to its small pore size, resulting in a decrease in membrane flux and a decrease in the retention rate of the effective ingredients in the earthworm extract. In addition, the ultrafiltration membrane used for extracting the effective ingredients of earthworms often has microorganisms adhering or depositing on the membrane surface to form a biofilm. The live bacteria on the membrane surface increase with the increase in the thickness of the biofilm, and the contamination layer becomes more compact due to its metabolites. Therefore, it is crucial to develop a hollow fiber earthworm ultrafiltration membrane material for Qilong capsules. Summary of the invention
[0004] The inventor has found that commercial polyethersulfone hollow fiber membranes, in the prior art, are to increase a hydrophilic layer on the surface of the membrane, but the ultrafiltration membrane itself has a small pore size, and increasing a hydrophilic layer on the surface will further cause the membrane pores to be blocked, thereby causing a decrease in flux. In order to solve the above problems, the present application compounds polyethersulfone, modified polyacrylonitrile, carboxylated polyethyleneimine, polyethylene glycol, functional filler, and glutaraldehyde to obtain hollow fiber earthworm ultrafiltration membranes for Qilong capsules, which ensures the pore size of the ultrafiltration membrane, further improves the hydrophilicity of the ultrafiltration membrane, reduces adsorption on its surface during the filtration process of earthworm extract, and ensures membrane flux. In addition, the adhesion and deposition of microorganisms on the membrane surface are reduced, the anti-pollution performance of the ultrafiltration membrane is improved, and the retention rate of the effective ingredients in the earthworm extract is further guaranteed.
[0005] On one hand, the present invention provides a hollow fiber earthworm ultrafiltration membrane for Qilong capsule, which comprises, by weight, 10-20 parts of polyethersulfone, 10-20 parts of modified polyacrylonitrile, 5-10 parts of carboxylated polyethyleneimine, 5-10 parts of polyethylene glycol, 2-7 parts of functional filler and 2-10 parts of glutaraldehyde.
[0006] Optionally, the preparation method of the modified polyacrylonitrile comprises the following steps:
[0007] S1: mixing polyacrylonitrile and N,N-dimethylformamide to react to obtain a first mixture;
[0008] S2: mixing the first mixture with hydroxylamine hydrochloride, adjusting the pH to 6, reacting at a temperature of 60-70° C., and then washing and drying to obtain modified polyacrylonitrile;
[0009] The mass ratio of polyacrylonitrile to N,N-dimethylformamide is 1:(4-7).
[0010] Furthermore, after polyacrylonitrile is modified with amidoxime, a large number of active groups such as hydroxyl and amino groups are generated on its molecular surface, which can react with polyethersulfone, carboxylated polyethyleneimine, polyethylene glycol, functional filler, and glutaraldehyde to produce a three-dimensional cross-linked network structure, thereby improving the mechanical properties and service life of the ultrafiltration membrane. In addition, the dispersibility and compatibility of the functional filler can be further improved, and the filtration accuracy of the ultrafiltration membrane for earthworm extract can be improved.
[0011] Optionally, the method for preparing the functional filler comprises the following steps:
[0012] (1) mixing the nanoparticles with dopamine hydrochloride and tris(hydroxymethyl)aminomethane solution, reacting at room temperature, washing, and drying to obtain an intermediate;
[0013] (2) adding the intermediate obtained in step (1) to a tris(hydroxymethyl)aminomethane solution, and then adding potassium salt of 3-sulfonyl methacrylate to react at room temperature, and washing and drying the product in turn to obtain a functional filler;
[0014] Among them, the nanoparticles are nano-silicon dioxide and nano-titanium dioxide;
[0015] The mass ratio of nanoparticles, dopamine hydrochloride and 3-sulfonate propyl methacrylate potassium salt is (1-3):1:(15-20).
[0016] Optionally, the mass ratio of the nanoparticles, dopamine hydrochloride, and 3-sulfonate propyl methacrylate potassium salt is (1-2):1:(18-20).
[0017] Further, there are a large number of hydroxyl groups on the surface of nano silicon dioxide, which has excellent super hydrophilicity, and nano titanium dioxide has extremely strong oxidizing ability and can achieve self-cleaning ability. But directly adding nanoparticles will reunite, resulting in poor dispersibility. The present application first coats the nanoparticles with polydopamine to improve its dispersibility, and reacts with 3-sulfonated propyl methacrylate potassium salt to make a large number of hydrophilic groups on its surface, further improving dispersibility. On the other hand, when carrying out a composite reaction with polyether sulfone, carboxylated polyethyleneimine, polyethylene glycol, and glutaraldehyde, a three-dimensional cross-linked network structure with higher intensity can be obtained, further improving the service life of the ultrafiltration membrane.
[0018] Optionally, the mass ratio of the nano-silicon dioxide to the nano-titanium dioxide is 1:(1-3).
[0019] Optionally, the particle sizes of nano silicon dioxide and nano titanium dioxide are both less than 100 nm.
[0020] Optionally, the mass ratio of polyethersulfone, modified polyacrylonitrile, carboxylated polyethyleneimine and functional filler is 3:3:1:1.
[0021] Optionally, the mixture further comprises 30-50 parts of a solvent, wherein the solvent is at least one of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide and N-methylpyrrolidone.
[0022] Another aspect of the present invention provides a preparation process of a hollow fiber earthworm ultrafiltration membrane for Qilong capsule, the preparation process comprising the following steps:
[0023] (1) reacting polyethersulfone, modified polyacrylonitrile, carboxylated polyethyleneimine, polyethylene glycol and functional filler at 40-70° C. in proportion to obtain a casting solution;
[0024] (2) pouring the casting solution into a spinning machine for spinning, soaking the obtained membrane filaments in a glutaraldehyde solution, cross-linking at a certain temperature, and then washing to obtain a hollow fiber earthworm ultrafiltration membrane for Qilong capsule. Furthermore, further cross-linking the obtained membrane filaments with glutaraldehyde can make the obtained ultrafiltration membrane more stable, the surface smoother, and further improve the membrane flux.
[0025] Optionally, the cross-linking temperature is 50-60°C.
[0026] Optionally, the mass fraction of the glutaraldehyde solution is 2-3%.
[0027] Compared with the prior art, the present invention achieves at least one of the following beneficial effects:
[0028] (1) The hollow fiber earthworm ultrafiltration membrane used in the Qilong capsule of the present invention improves the hydrophilicity of the ultrafiltration membrane, reduces the adsorption of earthworm extract on its surface during the filtration process, and ensures the membrane flux. In addition, it also reduces the adhesion and deposition of microorganisms on the membrane surface, improves the anti-pollution performance of the ultrafiltration membrane, and further ensures the retention rate of the effective ingredients in the earthworm extract.
[0029] (2) After the polyacrylonitrile in the hollow fiber earthworm ultrafiltration membrane for Qilong capsule of the present invention is modified by amidoxime, a large number of active groups such as hydroxyl and amino groups are generated on the molecular surface, which can react with polyethersulfone, carboxylated polyethyleneimine, polyethylene glycol, functional filler and glutaraldehyde to produce a three-dimensional cross-linked network structure, thereby improving the mechanical properties and service life of the ultrafiltration membrane. In addition, the dispersibility and compatibility of the functional filler can be further improved, and the filtration accuracy of the ultrafiltration membrane for earthworm extract can be improved.
[0030] (3) In the hollow fiber earth dragon ultrafiltration membrane for Qilong capsule of the present invention, the nanoparticles are first coated with polydopamine to improve their dispersibility, and reacted with 3-sulfonyl methacrylate potassium salt to obtain a functional filler, so that a large number of hydrophilic groups are present on the surface, further improving the dispersibility of the nanoparticles. On the other hand, when it is compounded with polyether sulfone, carboxylated polyethyleneimine, polyethylene glycol, and glutaraldehyde, a three-dimensional cross-linked network structure with higher strength can be obtained, further improving the service life of the ultrafiltration membrane. DETAILED DESCRIPTION
[0031] In order to more clearly illustrate the overall concept of the present invention, a detailed description is given below in an illustrative manner in conjunction with the specification.
[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0033] Example 1
[0034] The hollow fiber earthworm ultrafiltration membrane used in Qilong Capsules is composed, by weight, of 10 parts of polyethersulfone, 10 parts of modified polyacrylonitrile, 5 parts of carboxylated polyethyleneimine, 5 parts of polyethylene glycol, 2 parts of nano-silicon dioxide with an average particle size of 50 nm, 2 parts of glutaraldehyde and 30 parts of N-methylpyrrolidone.
[0035] The preparation method of modified polyacrylonitrile comprises the following steps:
[0036] S1: mixing polyacrylonitrile and N,N-dimethylformamide at a mass ratio of 1:4 to obtain a first mixture;
[0037] S2: The first mixture is mixed with 40 g / L hydroxylamine hydrochloride, the pH is adjusted to 6, the mixture is reacted at 60° C., and then the mixture is washed and dried to obtain modified polyacrylonitrile.
[0038] The preparation process of hollow fiber earthworm ultrafiltration membrane for Qilong capsule comprises the following steps:
[0039] (1) reacting polyethersulfone, modified polyacrylonitrile, carboxylated polyethyleneimine, polyethylene glycol, nano-silicon dioxide and N-methylpyrrolidone at 40° C. in proportion to obtain a casting solution;
[0040] (2) pouring the casting solution into a spinning machine for spinning, soaking the obtained membrane fibers in a 2% by mass glutaraldehyde solution, cross-linking at 50° C., and then washing to obtain a hollow fiber earthworm ultrafiltration membrane for Qilong capsule.
[0041] Example 2
[0042] The hollow fiber earthworm ultrafiltration membrane used in Qilong Capsule is composed of 20 parts of polyethersulfone, 20 parts of modified polyacrylonitrile, 10 parts of carboxylated polyethyleneimine, 10 parts of polyethylene glycol, 2 parts of nano titanium dioxide with an average particle size of 40nm, 2 parts of glutaraldehyde and 50 parts of N-methylpyrrolidone, by weight.
[0043] The preparation method of modified polyacrylonitrile comprises the following steps:
[0044] S1: mixing polyacrylonitrile and N,N-dimethylformamide at a mass ratio of 1:7 to obtain a first mixture;
[0045] S2: The first mixture is mixed with 40 g / L hydroxylamine hydrochloride, the pH is adjusted to 6, the mixture is reacted at 70° C., and then the mixture is washed and dried to obtain modified polyacrylonitrile.
[0046] The preparation process of hollow fiber earthworm ultrafiltration membrane for Qilong capsule comprises the following steps:
[0047] (1) reacting polyethersulfone, modified polyacrylonitrile, carboxylated polyethyleneimine, polyethylene glycol, nano-titanium dioxide and N,N-dimethylformamide at 70° C. in proportion to obtain a casting solution;
[0048] (2) pouring the casting solution into a spinning machine for spinning, soaking the obtained membrane fibers in a 3% by mass glutaraldehyde solution, cross-linking at 60° C., and then washing to obtain a hollow fiber earthworm ultrafiltration membrane for Qilong capsule.
[0049] Example 3
[0050] The hollow fiber earthworm ultrafiltration membrane used in Qilong Capsule is composed of 15 parts of polyethersulfone, 15 parts of modified polyacrylonitrile, 5 parts of carboxylated polyethyleneimine, 8 parts of polyethylene glycol, 5 parts of nano titanium dioxide with an average particle size of 40nm, 5 parts of glutaraldehyde and 40 parts of N-methylpyrrolidone, by weight.
[0051] The preparation method of modified polyacrylonitrile comprises the following steps:
[0052] S1: mixing polyacrylonitrile and N,N-dimethylformamide at a mass ratio of 1:5 to obtain a first mixture;
[0053] S2: The first mixture is mixed with 40 g / L hydroxylamine hydrochloride, the pH is adjusted to 6, the mixture is reacted at 65° C., and then the mixture is washed and dried to obtain modified polyacrylonitrile.
[0054] The preparation process of hollow fiber earthworm ultrafiltration membrane for Qilong capsule comprises the following steps:
[0055] (1) reacting polyethersulfone, modified polyacrylonitrile, carboxylated polyethyleneimine, polyethylene glycol, nano-titanium dioxide and N,N-dimethylacetamide at 50° C. in proportion to obtain a casting solution;
[0056] (2) pouring the casting solution into a spinning machine for spinning, soaking the obtained membrane fibers in a 3% by mass glutaraldehyde solution, cross-linking at 55° C., and then washing to obtain a hollow fiber earthworm ultrafiltration membrane for Qilong capsule.
[0057] Example 4
[0058] Based on Example 3, the main difference is that the preparation method of the functional filler comprises the following steps:
[0059] (1) 4 mg of the nanoparticles were mixed with 4 mg of dopamine hydrochloride and 80 ml of 0.1 mol / L tris(hydroxymethyl)aminomethane solution, reacted at room temperature, washed and dried to obtain an intermediate;
[0060] (2) adding the intermediate obtained in step (1) into 40 ml of tris(hydroxymethyl)aminomethane solution, and then adding 60 mg of 3-sulfonic acid propyl methacrylate potassium salt, reacting at room temperature (25° C.), and washing and drying the product in turn to obtain a functional filler;
[0061] The nanoparticles are nano-silicon dioxide and nano-titanium dioxide; the mass ratio of nano-silicon dioxide to nano-titanium dioxide is 1:1, and the average particle sizes of nano-silicon dioxide and nano-titanium dioxide are both 50nm.
[0062] Example 5
[0063] Based on Example 3, the main difference is that the preparation method of the functional filler comprises the following steps:
[0064] (1) 12 mg of the nanoparticles were mixed with 4 mg of dopamine hydrochloride and 80 ml of 0.1 mol / L tris(hydroxymethyl)aminomethane solution, reacted at room temperature, and washed and dried to obtain an intermediate;
[0065] (2) adding the intermediate obtained in step (1) to 40 ml of tris(hydroxymethyl)aminomethane solution, and then adding 80 mg of 3-sulfonic acid propyl methacrylate potassium salt, reacting at room temperature (25° C.), and washing and drying the product in turn to obtain a functional filler;
[0066] The nanoparticles are nano-silicon dioxide and nano-titanium dioxide; the mass ratio of nano-silicon dioxide to nano-titanium dioxide is 1:3, and the average particle sizes of nano-silicon dioxide and nano-titanium dioxide are both 50 nm.
[0067] Example 6
[0068] Based on Example 3, the main difference is that the preparation method of the functional filler comprises the following steps:
[0069] (1) 8 mg of the nanoparticles were mixed with 4 mg of dopamine hydrochloride and 80 ml of 0.1 mol / L tris(hydroxymethyl)aminomethane solution, reacted at room temperature, and washed and dried to obtain an intermediate;
[0070] (2) adding the intermediate obtained in step (1) into 40 ml of tris(hydroxymethyl)aminomethane solution, and then adding 70 mg of 3-sulfonic acid propyl methacrylate potassium salt, reacting at room temperature (25° C.), and washing and drying the product in turn to obtain a functional filler;
[0071] The nanoparticles are nano-silicon dioxide and nano-titanium dioxide; the mass ratio of nano-silicon dioxide to nano-titanium dioxide is 1:2, and the average particle sizes of nano-silicon dioxide and nano-titanium dioxide are both 70nm.
[0072] Example 7
[0073] Based on Example 1, the main difference is that the average particle size of nano-silicon dioxide is 200 nm.
[0074] Comparative Example 1
[0075] Based on Example 1, the main difference is that polyacrylonitrile is not modified.
[0076] Comparative Example 2
[0077] The main difference from Example 1 is that no functional filler is added.
[0078] Comparative Example 3
[0079] Based on Example 1, the main difference is that 20 parts of carboxylated polyethyleneimine are used.
[0080] Comparative Example 4
[0081] Based on Example 4, the main difference is that glutaraldehyde is not added.
[0082] Test Case
[0083] The method for determining the pure water flux is as follows: using a hollow fiber ultrafiltration membrane flux test device, the Qilong capsule prepared in this application is pre-pressed with a hollow fiber earthworm ultrafiltration membrane at 0.1 MPa for 30 minutes, and then within the test time t, the water production volume is V, the membrane filtration area is S, and the purified water flux is J = V / St, where V is in L, t is in h, and S is in m 2 The average flux of three different membrane filaments in the same batch is taken as the flux of the membrane filaments in this batch.
[0084] The method for determining the pure water flux recovery rate is as follows: the earthworm extract is ultrafiltered using the hollow fiber earthworm ultrafiltration membrane of the Qilong capsule prepared in the present application, the ultrafiltration membrane is taken out after the effective ingredient interception experiment in the earthworm extract, the contaminated ultrafiltration membrane is cleaned with pure water for 10 minutes, the pure water flux is measured again at 0.1Mpa, and the pure water flux is compared with the pure water flux of the ultrafiltration membrane that has not been ultrafiltered with the earthworm extract to obtain the pure water flux recovery rate.
[0085] The membrane flux and mechanical properties of the hollow fiber earthworm ultrafiltration membrane for Qilong capsule prepared in the present application are shown in Table 1.
[0086] Table 1
[0087]
[0088] As shown in Table 1, the water flux of the hollow fiber earthworm ultrafiltration membrane for Qilong capsule prepared in this application is not less than 800L / (m 2 h), the pure water flux recovery rate is not less than 90%, and the tensile strength is not less than 10MPa. The hollow fiber earthworm ultrafiltration membrane for Qilong capsule prepared by the present application improves the hydrophilicity of the ultrafiltration membrane, reduces the adsorption of earthworm extract on its surface during the filtration process, and ensures the membrane flux. At the same time, it reduces the adhesion and deposition of microorganisms on the membrane surface, improves the anti-pollution performance of the ultrafiltration membrane, and further ensures the retention rate of the effective ingredients in the earthworm extract. In addition, the ultrafiltration membrane prepared by the present application has good mechanical properties and service life (within 1 year of use, the pure water flux recovery rate is not less than 85%).
[0089] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A hollow fiber earthworm ultrafiltration membrane for Qilong capsule, characterized in that: By weight, the invention comprises 10-20 parts of polyethersulfone, 10-20 parts of modified polyacrylonitrile, 5-10 parts of carboxylated polyethyleneimine, 5-10 parts of polyethylene glycol, 2-7 parts of functional filler and 2-10 parts of glutaraldehyde.
2. The hollow fiber earthworm ultrafiltration membrane for Qilong capsule according to claim 1, characterized in that: The preparation method of the modified polyacrylonitrile comprises the following steps: S1: mixing polyacrylonitrile and N,N-dimethylformamide to react to obtain a first mixture; S2: mixing the first mixture with hydroxylamine hydrochloride, adjusting the pH to 6, reacting at a temperature of 60-70° C., and then washing and drying to obtain modified polyacrylonitrile; The mass ratio of polyacrylonitrile to N,N-dimethylformamide is 1:(4-7).
3. The hollow fiber earthworm ultrafiltration membrane for Qilong capsule according to claim 1, characterized in that: The preparation method of the functional filler comprises the following steps: (1) mixing the nanoparticles with dopamine hydrochloride and tris(hydroxymethyl)aminomethane solution, reacting at room temperature, washing and drying to obtain an intermediate; (2) adding the intermediate obtained in step (1) to a tris(hydroxymethyl)aminomethane solution, and then adding potassium salt of 3-sulfonyl methacrylate to react at room temperature, and washing and drying the product in turn to obtain a functional filler; Among them, the nanoparticles are nano-silicon dioxide and nano-titanium dioxide; The mass ratio of nanoparticles, dopamine hydrochloride and 3-sulfonate propyl methacrylate potassium salt is (1-3):1:(15-20).
4. The hollow fiber earthworm ultrafiltration membrane for Qilong capsule according to claim 3, characterized in that: The mass ratio of the nano silicon dioxide to the nano titanium dioxide is 1:(1-3).
5. The hollow fiber earthworm ultrafiltration membrane for Qilong capsule according to claim 3, characterized in that: The particle sizes of nano-silicon dioxide and nano-titanium dioxide are both less than 100nm.
6. The hollow fiber earthworm ultrafiltration membrane for Qilong capsule according to claim 1, characterized in that: The mass ratio of polyethersulfone, modified polyacrylonitrile, carboxylated polyethyleneimine and functional filler is 3:3:1:
1.
7. The hollow fiber earthworm ultrafiltration membrane for Qilong capsule according to claim 1, characterized in that: The invention also comprises 30-50 parts of a solvent, wherein the solvent is at least one of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide and N-methylpyrrolidone.
8. A process for preparing hollow fiber earthworm ultrafiltration membrane for Qilong capsule according to any one of claims 1 to 7, characterized in that: The preparation process comprises the following steps: (1) reacting polyethersulfone, modified polyacrylonitrile, carboxylated polyethyleneimine, polyethylene glycol and functional filler at 40-70° C. in proportion to obtain a casting solution; (2) pouring the casting solution into a spinning machine for spinning, soaking the obtained membrane fibers in a glutaraldehyde solution, cross-linking at a certain temperature, and then washing to obtain a hollow fiber earthworm ultrafiltration membrane for Qilong capsule.
9. The preparation process according to claim 8, characterized in that: The crosslinking temperature is 50-60°C.
10. The preparation process according to claim 8, characterized in that: The mass fraction of the glutaraldehyde solution is 2%-3%.